Programa “Daditex” basado en el enfoque lúdico para la Producción de Textos Cortos en Educación Primaria - Rojas Milla, Rosa Sheily (2017)
The general objective of the present investigation was: To determine the degree of influence of the program "daditex" with playful approach in the production of short texts in the children of 4th grade of Primary Education of the I.E. Nº 81011 Antonio Raimondi - Trujillo in 2016. And the hypothesis: The application of the "daditex" program based on the ludic approach significantly improves the production of short texts in the 4th grade primary school children of the I.E. Nº 81011 Antonio Raimondi - Trujillo in 2016._x000D_ The type of research was applied and experimental level. We worked with a non-probabilistic design. We worked with a population of 103 fourth grade students, taking a non-probabilistic sample for the convenience of 73 fourth grade students in the communication area of Educational Institution No. 81011 Antonio Raimondi of the primary level._x000D_ The research was developed in the second and third bimester of the academic year 2016, whose data were processed by the program the program SPSS version 16.0, and analyzed by means of the summary statistic with measurements of centrality through frequencies and by statistic for metrics through The student's t test, on the basis of which and the theoretical framework the respective discussion is carried out; It being determined that the application of the "daditex" program based on the playful approach significantly improves the production of short texts in children of the 4th grade of Primary Education in the I.E. Nº 81011 Antonio Raimondi in the year 2016.